Identification of Flowering-Related Genes Responsible for Differences in Bolting Time between Two Radish Inbred Lines - Jung, Won Yong; Park, Hyun Ji; Lee, Areum; Lee, Sang Sook; Kim, Youn-Sung; Cho, Hye Sun (Frontiers in Plant Science, 2016)
Late bolting after cold exposure is an economically important characteristic of radish (Raphanus sativus L.), an important Brassicaceae root vegetable crop. However, little information is available regarding the genes and pathways that govern flowering time in this species. We performed high-throughput RNA sequencing analysis to elucidate the molecular mechanisms that determine the differences in flowering times between two radish lines, NH-JS1 (late bolting) and NH-JS2 (early bolting). In total, 71,188 unigenes were identified by reference-guided assembly, of which 309, 788, and 980 genes were differentially expressed between the two inbred lines after 0, 15, and 35 days of vernalization, respectively. Among these genes, 218 homologs of Arabidopsis flowering-time (Ft) genes were identified in the radish, and 49 of these genes were differentially expressed between the two radish lines in the presence or absence of vernalization treatment. Most of the Ft genes up-regulated in NH-JS1 vs NH-JS2 were repressors of flowering, such as RsFLC, consistent with the late-bolting phenotype of NH-JS1. Although the functions of genes down-regulated in NH-JS1 were less consistent with late-bolting characteristics than the up-regulated Ft genes, several Ft enhancer genes, including RsSOC1, a key floral integrator, showed an appropriate expression to the late-bolting phenotype. In addition, the patterns of gene expression related to the vernalization pathway closely corresponded with the different bolting times of the two inbred lines. These results suggest that the vernalization pathway is conserved between radish and Arabidopsis.